2010
DOI: 10.1007/s10750-010-0420-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the diatom oxylipin 15S-HEPE on the reproductive success of the copepod Temora stylifera

Abstract: The copepod Temora stylifera was fed with the pennate diatom Pseudo-nitzschia delicatissima for 15 days. This diatom does not produce polyunsaturated aldehydes (PUAs) but only synthesizes other oxylipins such as the hydroxyacid (5Z,8Z,11Z,13E,15S,17Z)-15-hydroxy-5,8,11,13,17-eicosapentaenoic acid (15S-HEPE). Effects of this monoalgal diet were compared to copepods fed with the PUA-producing diatom Skeletonema marinoi and the control dinoflagellate Prorocentrum minimum which does not produce any oxylipins. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
4
25
0
2
Order By: Relevance
“…In 2005, total oxylipin levels were three times as high as in 2004, providing an explanation for the almost 25% reduction in hatching success in 2005 compared to 2004. These findings support laboratory studies (Barreiro et al, 2011;Fontana et al, 2007;Ianora et al, 2011b) showing that NVOs can induce negative effects comparable to those of PUAs. What remains unknown is why NVO levels in the phytoplankton vary from year-to-year.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In 2005, total oxylipin levels were three times as high as in 2004, providing an explanation for the almost 25% reduction in hatching success in 2005 compared to 2004. These findings support laboratory studies (Barreiro et al, 2011;Fontana et al, 2007;Ianora et al, 2011b) showing that NVOs can induce negative effects comparable to those of PUAs. What remains unknown is why NVO levels in the phytoplankton vary from year-to-year.…”
Section: Discussionsupporting
confidence: 89%
“…One of these compounds, 15S-HEPE, acts similarly to PUAs in that it induces malformations in newlyhatched nauplii and arrests embryogenesis at elevated concentrations (Ianora et al, 2011b). Interestingly, many diatom species seem to produce only these NVOs and not PUAs (Barreiro et al, 2011;Cutignano and Lamari, 2011;d'Ippolito et al, 2009;Fontana et al, 2007;Nanjappa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Teratogenic impacts (birth defects and hatching of malformed larvae) have also been recorded when females are fed with certain diatom diets (Poulet et al, 1995(Poulet et al, , 2007Uye, 1996;Ianora et al, 2011). In our study, 45-93% reduction was observed in nauplii production with increasing concentrations of decadienal.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have reported that exposure of embryos and larvae to PUA can severely impact development, growth and fitness of other copepod species (Miralto et al, 1999;Caldwell et al, 2002;Carotenuto et al, 2002;Ianora et al, 2004Ianora et al, , 2011Vargas et al, 2006;Poulet et al, 2007;Kâ et al, 2014). Decadienal has also been shown to potentially impact other marine organisms (Romano et al, , 2010Caldwell et al, 2005;Tosti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies on copepod nauplii reported in [12], this metabolite inhibited the cleavage in sea urchin Paracentrotus lividus embryos at concentrations higher than 70 µM and induced 100% blockage of cellular division at 94 µM (Figure 1a). Nevertheless, the methyl ester of 15( S )-HEPE ( 2 ) showed a noticeably higher activity (IC50 = 4.1 µM) and completely arrested division of treated embryos at only 8 µM.…”
Section: Resultssupporting
confidence: 92%